Managing North-South Research Collaboration Projects During the COVID-19 Pandemic : An Empirical Study - Sowe, Sulayman K.; Schönfeld, Mirco; Samimi, Cyrus; Steiner, Petra; Schürer-Ries, Anke (International Journal of Information Technology Project Management, 2022)
Researchers from the Global North and South have collaborated for decades to conduct cutting-edge interdisciplinary research. The tools they used to manage their research projects remained virtually unchanged until the COVID-19 pandemic outbreak early in 2020. Since then, a lot has changed, including the nature and dynamics of research collaboration. How are researchers and project managers adapting to this change? Survey data, semi-structured interviews, and personal accounts from 102 respondents from 33 countries are used in this empirical study to investigate the impact of the pandemic on research collaboration projects. An independent non-parametric t-test revealed a significant difference in the research collaboration infrastructure and home environment between Global North and global South collaborators. The findings have practical implications for people involved in collaborative research projects, funding agencies, project management professionals, and universities interested in pursuing or sustaining North-South research collaboration during the pandemic.